Visual Analysis of Uterine Adhesion Research Based on CiteSpace: Bibliometric Analysis From 2006 to 2021 - Ding, Dou-Dou; Zuo, Man-Zhen; Zhou, Quan; He, Ze-Xian (Frontiers in Reproductive Health, 2022)
Background Intrauterine adhesionis caused by a variety of reasons, such as damage of the endometrial basal layer, adhesion or occlusion of the uterine cavity or cervix in different degrees. Seriously endangering women's physical and mental health. Objective The purpose of this paper is to analyze the research development of intrauterine adhesions in recent 15 years, explore the future development direction, and promote the development of this field. Methods With intrauterine adhesions and Ashman's syndrome as the theme, the related literatures from January 2006 to July 2021 in the Web of Science were searched, and the visual atlas was analyzed by CiteSpace software. Results A total of 644 literatures were included. The key words related to intrauterine adhesion mainly include adhesion, pregnancy, expression, intrauterine adhesions, women, adhesion molecule, diagnosis, activation, hysteroscopy and fertility, etc. Six clusters were obtained by keywords analysis, involving hysteroscopy, placenta, office hysteroscopy, uterus and laparoscopy. Co-occurrence of keywords shows that the research focus in recent years is on endometrial repair and regeneration. Conclusions Through the bibliometric analysis of WOS research on intrauterine adhesions in recent 15 years, the comprehensive analysis of countries, institutions, authors and keywords is obtained, which has a clear guiding significance for guiding the future development of intrauterine adhesions.